Effects of family and school on academic achievement of korean high school students - Seo , In Seog; Kim , Kioh (Journal of Interdisciplinary Studies in Education, 2014)
This study examines the influence of family and school on vocational high school students’ academic achievement in South Korea. A nationally representative sample from the Korean Education and Employment Panel Survey (KEEP) was analyzed. Results show that variables related to parents did not influence Korean vocational high school students’ academic achievement. School facility did not have any influence on the general subject academic achievement, but it impacted the vocational subject academic achievement of Korean students. Two school related variables - teacher ability and relationship were significant for academic achievement.